Disparity in the Setting of Incident Heart Failure Diagnosis. (27th July 2021) - Sandhu, Alexander T.; Tisdale, Rebecca L.; Rodriguez, Fatima; Stafford, Randall S.; Maron, David J.; Hernandez-Boussard, Tina; Lewis, Eldrin; Heidenreich, Paul A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Early heart failure (HF) recognition can reduce morbidity, yet HF is often initially diagnosed only after a patient clinically worsens. We sought to identify characteristics that predict diagnosis in the acute care setting versus the outpatient setting. Methods: We estimated the proportion of incident HF diagnosed in the acute care setting (inpatient hospital or emergency department) versus outpatient setting based on diagnostic codes from a claims database covering commercial insurance and Medicare Advantage between 2003 and 2019. After excluding new-onset HF potentially caused by a concurrent acute cause (eg, acute myocardial infarction), we identified demographic, clinical, and socioeconomic predictors of diagnosis setting. Patients were linked to their primary care clinicians to evaluate diagnosis setting variation across clinicians. Results: Of 959 438 patients with new HF, 38% were diagnosed in acute care. Of these, 46% had potential HF symptoms in the prior 6 months. Over time, the relative odds of acute care diagnosis increased by 3.2% annually after adjustment for patient characteristics (95% CI, 3.1%–3.3%). Acute care diagnosis setting was more likely for women compared with men (adjusted odds ratio, 1.11 [95% CI, 1.10–1.12]) and for Black patients compared with White patients (adjusted odds ratio, 1.18 [95% CI, 1.16–1.19]). The proportion of acute care diagnosis varied substantially (interquartile range: 24%–39%) among clinicians after adjusting for patient-level risk factors. Conclusions: A large proportion of first HF diagnoses occur in the acute care setting, particularly among women and Black patients, yet many had potential HF symptoms in the months before acute care visits. These results raise concerns that many HF diagnoses are missed in the outpatient setting. Earlier diagnosis could allow for timelier high-value interventions, addressing disparities and reducing the progression of HF.